Inside Cover: 2‐(Pyridinium‐1‐yl)‐1, 1‐bis(perfluoroalkylsulfonyl)ethan‐1‐ide: A Practical Reagent for Synthesis of Strongly Acidic 1, 1‐Bis(perfluoroalkylsulfonyl)alkanes (Chem. Eur. J. 34/2017). Issue 34 (20th April 2017) - Yanai, Hikaru; Takahashi, Ryuta; Takahashi, Yoichi; Kotani, Akira; Hakamata, Hideki; Matsumoto, Takashi
Abstract : A shelf‐stable, easy‐to‐handle reagent for the in situ generation of the highly electrophilic alkene (Rf SO2 )2 C=CH2 was developed. By using this reagent, a new type of superacidic molecule was successfully synthesized. The authors also found some synthetic reactions catalyzed by the alkene. Detailed NMR studies revealed a rapid decomposition rate (milliseconds order) of the reagent to generate (Rf SO2 )2 C=CH2 /2‐fluoropyridine. In this picture, the rapid formation of (Rf SO2 )2 C=CH2 is represented by cracking open a raw egg. This egg is also a symbol for the birth of new chemistry. More information can be found in the Full Paper by H. Yanai, T. Matusmoto et al. onpage 8203 .